Knockdown of GmD53a confers strigolactones mediated rhizobia interaction and promotes nodulation in soybean - Naveed Rehman; Fahim Ullah Khan; Muhammad Imran; Shahid Ali Rajput; Yiming Li; Ihteram Ullah; Rana waseem Akhtar; Muhammad Imran; Arwa Abdulkreem AL-Huqail; Ahmad El Askary; Amany Salah Khalifa; Muhammad Tehseen Azhar (PeerJ, 2022)
Background Strigolactones (SLs) play a key role in modulating plant root growth, shoot branching, and plant-symbiont interaction. However, despite their significance, the components of SL biosynthesis and signaling in soybean and their role in soybean-rhizobia interaction is unknown. Methods In this study, we identified and functionally characterized the GmD53a from soybean. The GmD53a ORFs were amplified from root cDNA using primers for GmD53a RNA interference. To induce transgenic hairy roots of soybean, electric shock was used to transform pB7WG1WG2 vectors containing GmD53a knockdown and GUS into K599 strains of Agrobacterium rhizogenes. The hairy roots and nodules were collected and examined for root nodules ratio and RNA was extracted after 4 weeks of rhizobia inoculation. Results A tissue-specific expression assay showed that GmD53a was differentially expressed in plant parts, predominantly in the stem and nodule. Furthermore, its expression was significantly up-regulated during rhizobia infection and varied with nodule formation. The GmD53a-knockdown chimerical plants were produced to further check its role in soybean nodulation in comparison with control GUS. In knockdown lines, the GmD53a (suppressor of strigolactone MAX2) has a higher number of nodules compared to control lines. Furthermore, the expression levels of several nodulation genes essential for initiation and formation of nodules were altered in GmD53a-knockdown lines. Conclusion The results revealed that SL biosynthesis and signaling are not conserved but also have close interaction between SL and legume rhizobia.